Cytosine arabinoside transport and metabolism in acute leukemias and T cell lymphoblastic lymphoma. - Wiley, J S; Taupin, J; Jamieson, G P; Snook, M; Sawyer, W H; Finch, L R (The Journal of Clinical Investigation, 1985)
Cytosine arabinoside (araC) has proven efficacy in acute myeloid leukemia (AML), but its place in the treatment of acute lymphoblastic leukemia (ALL) and T lymphoblastic lymphoma is uncertain. The therapeutic potential of araC has been assessed in patients with AML, ALL, and T lymphoblastic lymphoma by measuring the conversion of araC to its active metabolite, the 5'-triphosphate of araC (araCTP), in purified blasts from patients as well as in normal polymorphs and lymphocytes. In all leukemias, araCTP was the major intracellular metabolite of araC. The highest araCTP formation was in blasts from T lymphoblastic lymphoma, which formed threefold more nucleotide than myeloblasts, and in turn myeloblasts formed twofold more araCTP than lymphoblasts from ALL. The mean araCTP formation in myeloblasts was sixfold greater than polymorphs, but in contrast, lymphoblasts and lymphocytes formed low and similar amounts of this nucleotide. Reasons for the sixfold range in araCTP accumulation in the various leukemic blasts were studied. The mean size of myeloblasts was 35-70% larger than lymphoblasts when compared on the basis of protein or intracellular water content, but T lymphoblastic lymphoma blasts and lymphoblasts were the same size. Activities of deoxycytidine kinase, deoxycytidylate deaminase, and pyrimidine nucleoside monophosphate kinase were not different between any of the leukemic cell types. The number of nucleoside transport sites on blasts was estimated by measuring the equilibrium binding of [3H]nitrobenzylthioinosine (NBMPR), which binds with high affinity to the transporter. Scatchard analysis yielded mean values of 27,500 sites/cell for T lymphoblastic lymphoma blasts, 10,000 sites/cell for myeloblasts, and 2,300 sites/cell for lymphoblasts. Our previous work has shown that araC influx correlates with the maximum number of 3H-NBMPR binding sites in leukemic and normal white cells. A strong correlation was observed between the number of nucleoside transport sites per leukemic blast cell and the accumulation of intracellular araCTP from extracellular araC at 1 microM. Membrane transport of araC at the low concentrations (approximately 1 microM), which are achieved therapeutically, is a major rate-limiting step in its conversion to araCTP by leukemic blast cells. Myeloblasts form more araCTP than lymphoblasts because of both higher nucleoside transport capacity and larger cell size. The highest nucleoside transport capacity and largest conversion of araC to araCTP is in T lymphoblastic lymphoma, which suggests that araC may be effective in the treatment of this disease.